MODE-SHAPE JEMBATAN CABLE STAYED SUNGAI DAREH - Ariono Dhanisworo Indra Budhi; Herdianto Arifin; Iwan Zarkasi (Jurnal HPJI (Himpunan Pengembangan Jalan Indonesia), 2020)
Abtract The Dareh River Bridge is a harp type cable stayed bridge with one symmetrical pylon. From the loading test it is known that the deflection in the middle of the span of the bridge is 55 mm, in the quarter span is 30 mm, and in three quarters the span is 32 mm. While the reverse deflection in the middle span is 27 mm, in a quarter span 20 mm, and in three quarters 23 mm span. These values are not significantly different from the value of the output given by the RM Bridge software, which is 56 mm in the middle span. After the model is matched, the Eigenvalue of RM Bridge is found, for the shape mode or half-span bending pattern, quarter-bending span, and torque. Then, these values are compared with the shape mode of the test results in the field, which for half the bending span produces a frequency of 1.18 Hz, a quarter of the bending span produces a frequency of 1.88 Hz, and a torque of 3.77 Hz, and the results are quite close. During the loading test, there was an explosion in the cable anchor area when the test load showed 240 tons, so the test was stopped at this point. This value is checked through the cable stress from the analysis of RM Bridge, and apparently there is no excessive stress, because the cable stress is only 262 MPa. Similarly, when loaded with the potential regional earthquake loads, the stress only increases to up to 313 MPa, which is still smaller than 0.45 fpu. Keywords: bridge, cable stayed, bridge deflection, reverse deflection, shape mode  Abstrak Jembatan Sungai Dareh adalah jembatan cable stayed tipe harp dengan satu pilon simetris. Dari hasil pengu-jian pembebanan diketahui bahwa lendutan di tengah bentang jembatan adalah 55 mm, di seperempat bentang adalah 30 mm, dan di tiga perempat bentang adalah 32 mm. Sedangkan lawan lendut di tengah bentang adalah 27 mm, di seperempat bentang 20 mm, dan di tiga perempat bentang 23 mm. Nilai-nilai ini tidak berbeda secara signifikan dibandingkan dengan nilai hasil keluaran perangkat lunak RM Bridge, yaitu 56 mm di tengah bentang. Setelah model dicocokkan, dicari Nilai Eigen dari RM Bridge, untuk mode shape atau pola setengah bentang bending, seperempat bentang bending, dan torsi. Kemudian nilai-nilai ini dibandingkan dengan mode shape hasil pengujian di lapangan, yang mana untuk setengah bentang bending menghasilkan frekuensi 1,18 Hz, seperempat bentang bending menghasilkan frekuensi 1,88 Hz, dan torsi 3,77 Hz, dan hasilnya cukup mendekati. Pada pengujian terjadi suara ledakan di area angkur kabel saat beban pengujian menunjukkan 240 ton, sehingga pengujian dihentikan pada angka 240 ton tersebut. Nilai ini diperiksa melalui tegangan kabel hasil analisis RM Bridge, dan ternyata tidak terjadi tegangan yang berlebihan, karena tegangan kabel hanya 262 MPa. Demikian pula bila dibebani dengan gempa yang ada di wilayah tersebut, tegangan hanya meningkat menjadi 313 MPa, yang masih lebih kecil daripada 0,45 fpu. Kata-kata kunci: jembatan, cable stayed, lendutan jembatan, lawan lendut, mode shape